KONSEP “AL-FASL” DAN “AL-WASL” ABID AL-JABIRI DAN APLIKASINYA PADA AYAT HIJAB - Suci Wulandari (Farabi, 2017)
Understanding the verses of the Koran must always be done to realizeKorans}ha>lih likulli al-zama>n wa al-maka>n. In the contemporary era, many scholars who appears and offers a variety of methodologies to understand the verses of the Koran. One of them wasA>bid al-Ja>biri. He offered the concept of al-Fas}l and al-Was}l. Construction al-Fas}l(فصل المقروء عن القارئ) is performed in order to obtain the original meaning of the verses of the Koran. Its steps consist of: a) Analysis of the text include the analysis horizon ما فى النص and ما حول النص, and b) Analysis mufassir’s horizon that includes experience, knowledge, tradition, and the context or reality. As for the construction of al-Was}l(إلى الواقع وصل القارئ) is to connect the text in the time down to the needs of the present. A>bid al-Ja>biri's offer will be applied to the verses that talk about the h}ija>b in order to see the extent of his methodology can be used to obtain a contextual understanding of the verses of Koran.